Definitive identification of a member of the Epstein-Barr virus nuclear protein 3 family. - Hennessy, K (1986)
Some Epstein-Barr virus (EBV) immune human antisera are known to react with a 142-kDa protein, EBV-encoded nuclear antigen 3 (EBNA3), which, like EBNA1 and EBNA2, is likely to be involved in the establishment of latent infection or growth transformation. We have now constructed gene fusions between Escherichia coli lacZ and an EBV DNA open reading frame (BERF1; BamHI E fragment rightward open reading frame 1), which is transcribed into an mRNA in latently infected cells. Purified hybrid protein from one of these constructs, chosen because of its reactivity with EBNA3-positive human antisera, was used to affinity purify the specific antibody from human antiserum. This specific antibody was used to prove that EBNA3 is encoded, at least in part, by BERF1, and that EBNA3 is in the nucleus of each latently infected cell. In rodent cells, BERF1 encodes a 120- to 130-kDa protein, which translocates to the nucleus and is recognized by EBNA3-positive human antisera. Two other proteins similar in size to EBNA3 are detected in latently infected cells by EBV immune human antisera. Two EBV open reading frames related to BERF1 may encode these proteins.